Faktor–Faktor yang Mempengaruhi Indeks Harga Saham Gabungan - Tegar Citra Asmara; Desmintari Desmintari; Indri Arrafi Juliannisa (Jurnal Indonesia Sosial Sains, 2022)
The Composite Stock Price Index is an indicator of stock price movements and also to measure the combined performance of all stocks listed on the Indonesia Stock Exchange, as well as being a guide in investing for investors. Many indicators can affect the Composite Stock Price Index, such as inflation, interest rates, gold prices, and world oil prices. This study aims to determine the effect of inflation, interest rates, gold prices, and also world oil prices on the Composite Stock Price Index. This study uses monthly data from 2012 – 2019. The method used in this study is a multiple linear regression analysis model using the OLS method. The results of multiple regression analysis show that (1) there is no influence between inflation on the Composite Stock Price Index (2) there is no influence between interest rates on the Composite Stock Price Index (3) there is an influence between the gold price on the Composite Stock Price Index (4) there is no there is an influence between world oil prices on the Composite Stock Price Index.